Application of Mental Relaxation Techniques (Mindful Breathing and Guided Imagery) in Managing Separation Anxiety among 7- to 11-Year-Old Primary School Children in Shiraz - Behineh, Fatemeh; Azari, Zahra (Iranian Journal of Neurodevelopmental Disorders, 2027)
Purpose: This study aimed to determine the effectiveness of mental relaxation techniques, including mindful breathing and guided imagery, in managing separation anxiety and its dimensions among 7- to 11-year-old primary school children in Shiraz. Methods and Materials: This applied study employed a quasi-experimental pretest–posttest design with an experimental group and a control group. The statistical population comprised primary school students aged 7–11 years in Shiraz during the 2026 academic year. Participants were recruited through convenience sampling and initially screened using the Separation Anxiety Assessment Scale developed by Eisen and Schaefer (1999). Thirty children who obtained the highest separation anxiety scores and met the eligibility criteria were selected and randomly assigned to an experimental group receiving mental relaxation training (n = 15) or a control group receiving no intervention (n = 15). The research instruments included the child separation anxiety-related disorders questionnaire and a mental relaxation training program based on mindful breathing and guided imagery. Data were analyzed using SPSS version 26 at descriptive and inferential levels. Analysis of covariance was used to compare posttest scores while controlling for pretest differences. Findings: The analysis of covariance indicated that participation in the mental relaxation program significantly reduced fear and physical symptoms, generalized separation anxiety, anxiety related to being alone, and social anxiety among children with separation anxiety compared with the control condition. However, the intervention did not produce a statistically significant reduction in school-phobia-related symptoms. Overall, the inferential findings supported the effectiveness of mindful breathing and guided imagery for most assessed dimensions of childhood separation anxiety. Conclusion: Mental relaxation techniques based on mindful breathing and guided imagery appear to be effective, accessible, and noninvasive strategies for reducing several major manifestations of separation anxiety in primary school children, although additional interventions may be required to address school phobia specifically.